PENINGKATAN PENGETAHUAN PENCEGAHAN SINDROM METABOLIK MELALUI PEMANFAATAN TANAMAN ROSELLA PADA LANSIA DI WILAYAH PUSKESMAS SETABELAN SURAKARTA DI MASSA COVID-19 - Dwi Sarbini; Farida Nur Isnaeni; Winda Wahyu Pratiwi; Dinda Agustin Sandra; Selfahyasa Raharjo; Izzatul Fajriyah; Tafara Fikrama Depriasa (GEMASSIKA: Jurnal Pengabdian Kepada Masyarakat, 2023)
The elderly is a process in life that is characterized by a decrease in one's body function to maintain balance against physiological stress conditions. The decline in health in the elderly is most often caused by non-communicable diseases. One of the non-communicable diseases is metabolic syndrome. Metabolic syndrome is a metabolic disorder that originates from a collection of various diseases such as cardiovascular disease, stroke, central obesity, impaired glucose tolerance, and dyslipidemia which may develop into diabetes. Rosella flowers have the benefit of lowering blood pressure, HbA1c, and other factors that cause metabolic syndrome because they contain organic acids, anthocyanins and flavonoids. The main problem faced by partners is the ignorance of the elderly to prevent complications of cardiovascular disease so that it becomes metabolic syndrome. This limitation causes the eating behavior of the elderly to often pay no attention to the type of food that can increase the risk of hypertension, obesity, and diabetes mellitus. Community service activities are carried out at the Waras Mulyo Posbindu in the Setabelan Health Center work area in October 2022 in Setabelan Village, Banjarsari District, Surakarta City. There were 20 elderly who took part in Posbindu Waras Mulyo. Held from 13.00-14.00. The results of the pretest and posttest were compared to find out if there was an increase in knowledge among the elderly. Based on the comparison results, it was found that 20 elderly people (100%) had increased knowledge. Increased knowledge of the elderly about understanding, risk factors, signs and symptoms, and how to prevent them. Keywords: Elderly; Metabolic Syndrome; Knowledge; Rosella.